Small Wind Power Potential in Six Cities at Gifu Prefecture, Japan. (February 2019) - Rahmat, A; Irwandani,; Diani, R; Yanda, R
Abstract: Wind energy is one of the economic renewable sources and a valuable supplement to conventional energy sources. Small wind power generator can be used for substitution of conventional energy source. The main objective of the present study is to estimate small wind power potential using wind speed data. The result shows, the highest maximum wind power potential was found in Gifu city it was 4.77 watt. However, the total wind power potential at 2016-2017 the highest is 50365.62 Kwh in Gero city and the lowest was found in Gujo city with only 884.32 Kwh. The potential for wind power was strongly influenced by the geological condition and seasonal change. The high the potential of small wind power found in March-May, this time changes the season from winter to spring or spring. Gero city, Gifu city, and Takayama city have the potential to install small wind power generator, but not recommended for Gujo city and Nakatsugawa city.